Switching Intentions: A Case of Saudi Arabian Hypermarkets - Samrena Jabeen; Abu Bakar Abdul Hamid; Saif Ur Rehman (International Journal of Economics and Financial Issues, 2015)
Switching intention (SI) of consumer is sought as main issue of retailing due to its negative effects on market share and profitability of retail outlet. Now firms need to know the factors, which contribute to choose another outlet, and customer changes its patronage elsewhere. For this reason, it is very important for firm to understand the reasons of consumer switching to maintain their long lasting relationship with customers. This study is about the impact of retail service quality on customer satisfaction (CS) by using retail service quality model and moderating role of ethnic store (ES) in SI of satisfied customers. The purpose of the paper is to looks into the determinants of SI and attempts to answer why satisfied customer switch and do not maintain the relationship with current store. Statistical population is the customers of hypermarket in Saudi Arabia. The research method is based on descriptive – survey and data analysis method is by structural equation modeling by using Amos software. Significant positive effect of dimensions of retail service quality model on CS is found. Moreover, the moderating role of store ethnicity is also proved for CS-SI links, which exhibits that store ethnicity affects the behavior of satisfied customers and they intend to switch to their ES.